Basin-scale stratigraphic correlation of late Pleistocene-Holocene (MIS 5e-MIS 1) strata across the rapidly subsiding Po Basin (northern Italy). (1st June 2020) - Campo, B.; Bruno, L.; Amorosi, A.
Abstract: Eight stratigraphic transects, 40–140 km long reveal, for the first time on a regional scale, a comprehensive picture of facies architecture of the highly preserved Late Pleistocene-Holocene sedimentary succession from the rapidly subsiding Po Basin. Facies analysis and pollen-based correlation, supported by radiocarbon, electron-spin resonance and optically stimulated luminescence dates, enabled the attribution of distinct stratigraphic intervals to Marine Isotope Stages (MIS) 6 to 1. Basin-scale facies changes appear to have been driven mostly by glacio-eustatic oscillations falling in the Milankovitch band (∼100 ky). The MIS 5e coastal wedge was tracked continuously beneath the modern shoreline, for over 110 km along strike. Along-dip (west-east) stratigraphic correlation over 140 km revealed the characteristic landward transition from shallow-marine and coastal facies to lagoonal, swamp, and floodplain deposits. The MIS 5d-MIS 2 stratigraphic succession, up to 95-m-thick, records the stepped, basinward shift of facies related to the post-MIS 5e sea-level fall. In particular, lagoon and swamp facies mark minor transgressions (Substages 5c and 5a), whereas thick floodplain deposits and laterally extensive (>40 km) fluvial channel-belts, up to 30 m thick, characterized the glacial periods (MIS 4 and MIS 2). The Holocene (MIS 1) coastal wedge shares many similarities in terms of facies architecture and geometry with its MIS 5e counterpart, though maximum landward marine incursion during the MIS 5e transgression was 10 km farther inland (36 km inland of modern shoreline). Organic-rich (freshwater swamp) environments developed > 100 km landwards of the present-day coastline. The MIS 5e-MIS 1 succession of the Po Basin displays an exceptional thickness, up to 130 m. Minimum values (∼20 m) are recorded close to the Apennine margin and above the buried actively growing anticlines. The spatial distribution and geometry of the MIS 5e-MIS 1 strata, as well as rapidly varying subsidence rates (from 0.2 to 1.0 mm/y) reflect the strong influence of the structural setting (location of major thrust fronts) over the creation/destruction of accommodation. Highlights: The stratigraphic architecture of the last 130 ky in the Po Basin was reconstructed. Along-strike and along-dip facies changes are emphasized through transects. Detailed facies mapping of the MIS 5e maximum marine ingression was carried out. MIS 5e-MIS 1 facies architecture clearly denotes a dominant glacio-eustatic control. Detailed stratigraphic correlations reveal a structural control on sedimentation.